2018
DOI: 10.1037/ccp0000318
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ posttraumatic stress and child adjustment problems in families seeking services for intimate partner violence.

Abstract: Addressing women's trauma symptoms at the point of seeking services for IPV has possible implications for child mental health. Attempting to reduce mothers' PTSSs may have positive effects for women as well as their children. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 73 publications
4
10
0
Order By: Relevance
“…They found that higher maternal PTSS was associated with greater child internalizing and externalizing problems, and that this relationship was maintained over time. Furthermore, a 5-year follow-up of this same sample found that, within families, changes in maternal PTSS led to changes in children’s internalizing and externalizing behavior problems (Jouriles et al, 2018a).…”
Section: Risk Factors For Ptss In Childrenmentioning
confidence: 98%
“…They found that higher maternal PTSS was associated with greater child internalizing and externalizing problems, and that this relationship was maintained over time. Furthermore, a 5-year follow-up of this same sample found that, within families, changes in maternal PTSS led to changes in children’s internalizing and externalizing behavior problems (Jouriles et al, 2018a).…”
Section: Risk Factors For Ptss In Childrenmentioning
confidence: 98%
“…IPV has been linked with a wide array of both physical and mental health effects such as depression, suicidality, posttraumatic stress disorder (PTSD), miscarriages, injuries, and, in severe cases, death (Devries et al, 2013; Mahenge et al, 2013; Mapayi et al, 2013; Stockl et al, 2013). Not only women get affected by IPV, their children and family’s economic wellbeing suffer as well (Adams et al, 2012; Jouriles et al, 2018; Neamah et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…; Saltzman, Fanslow, McMahon, & Shelley, 2002). Decades of research have clearly established the association between IPV exposure and maladaptive child outcomes, including externalizing (e.g., disruptive and aggressive behaviors; Fantuzzo, Boruch, Beriama, Atkins, & Marcus, 1997; Glass, Kohli, Surkan, Remy, & Perrin, 2018) and internalizing symptoms (e.g., depression and anxiety; Grych, Jouriles, Swank, McDonald, & Norwood, 2000; Jouriles et al, 2018), as well as posttraumatic stress symptoms (Bogat, DeJonghe, Levendosky, Davidson, & von Eye, 2006) and dissociative symptoms (Stride, Geffner, & Lincoln, 2008). Furthermore, some studies suggest 40% to 60% of school-aged children that have witnessed IPV display clinically diagnosable levels of emotional and/or behavioral problems (Graham-Bermann, Gruber, Howell, & Girz, 2009; Grych, Fincham, et al, 2000).…”
Section: Introductionmentioning
confidence: 99%